Fascin-1 is Highly Expressed Specifically in Microglia After Spinal Cord Injury and Regulates Microglial Migration - Yu, Shuisheng; Cheng, Li; Tian, Dasheng; Li, Ziyu; Yao, Fei; Luo, Yang; Liu, Yanchang; Zhu, Zhenyu; Zheng, Meige; Jing, Juehua (Frontiers in Pharmacology, 2021)
Recent research indicates that after spinal cord injury (SCI), microglia accumulate at the borders of lesions between astrocytic and fibrotic scars and perform inflammation-limiting and neuroprotective functions, however, the mechanism of microglial migration remains unclear. Fascin-1 is a key actin-bundling protein that regulates cell migration, invasion and adhesion, but its role during SCI has not been reported. Here, we found that at 7-14 days after SCI in mice, Fascin-1 is significantly upregulated, mainly distributed around the lesion, and specifically expressed in CX3CR1-positive microglia. However, Fascin-1 is not expressed in GFAP-positive astrocytes, NeuN-positive neurons, NG2-positive cells, PDGFRβ-positive cells, or blood-derived Mac2-positive macrophages infiltrating into the lesion core. The expression of Fascin-1 is correspondingly decreased after microglia are specifically depleted in the injured spinal cord by the colony-stimulating factor 1 receptor (CSF1R) inhibitor PLX5622. The upregulation of Fascin-1 expression is observed when microglia are activated by myelin debris in vitro, and microglial migration is prominently increased. The inhibition of Fascin-1 expression using small interfering RNA (siRNA) markedly suppresses the migration of microglia, but this effect can be reversed by treatment with myelin. The M1/M2-like polarization of microglia does not affect the expression of Fascin-1. Together, our results suggest that Fascin-1 is highly expressed specifically in microglia after SCI and can play an important role in the migration of microglia and the formation of microglial scars. Hence, the elucidation of this mechanism will provide novel therapeutic targets for the treatment of SCI.